THE USE OF PEPACCUR LOCAL WISDOM FOR INDONESIAN LITERARY TEACHING MATERIALS - Fuad, Muhammad; Efendi, Anwar; Muhammad, Ulul Azmi (JPI (Jurnal Pendidikan Indonesia), 2020)
Cultural diversity that exists in various regions in Indonesia produces a lot of potential for local wisdom and tradition. Various Indonesian local wisdoms have been used as teaching material in the classroom. However, pepaccur local wisdom is still rarely known and used as teaching material. Therefore it is a novelty to turn pepaccur local wisdom into Indonesian literary teaching materials. This study aims to investigate the properness of pepaccur local wisdom for Indonesian literary teaching materials. The qualitative approach used in this study is characterized by collecting data through interviews, observation, recording and book review, and other sources related to pepaccur local wisdom. Content analyses were also used in analyzing the collected data. The results of this study are in the form of pepaccur presentations that are appropriate to be used as teaching materials for Indonesia language and literature based on the characteristics of the functions and values of local wisdom contained in them. Values contained in pepaccur such as religion, simplicity, cooperation and politeness can be a reference in behaving in the community and this integration can be an effort to preserve local wisdom that has begun to be abandoned by the Lampung community. Implications from this study, through pepaccur-based teaching materials, students can learn to live a simple life, have a community with mutual help and respect, and learn poetic arts to provide entertainment and advice.